2010
DOI: 10.1292/jvms.10-0165
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibilities of Four Species of Mycoplasma Isolated in 2008 and 2009 from Cattle in Japan

Abstract: ABSTRACT. We examined the susceptibility in vitro of 99 isolates of Mycoplasma (M. bovirhinis, M. bovis, M. alkalescens and M. bovoculi) and one of Acholeplasma laidlawii collected in 2008 and 2009 from Japanese homebred cattle and cows imported from Australia to 13 antimicrobial agents. Mycoplasma species isolated from homebred cattle were susceptible to spectinomycin and fluoroquinolones but resistant to macrolides, tetracyclines, thiamphenicol and flumequine. Kanamycin, lincomycin and chloramphenicol main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 11 publications
7
34
0
Order By: Relevance
“…Three studies reported highly resistant isolates, with MICs of ÏŸ8 g/ml, in the United Kingdom, Japan, and Belgium (9-11), while several others indicated a low to no increase in resistance, except for a few isolates, in Japan, the United States, and several European countries (6,(12)(13)(14)(15). Some of these studies involved isolates collected before 2005 (11, 13), but the majority referred to recent ones (6,9,10,12,14,15), suggesting a recent phenomenon. In the United Kingdom, a shift of resistance from an MIC 90 of 1 g/ml to one of 32 g/ml occurred during the last decade (9, 16).…”
mentioning
confidence: 99%
“…Three studies reported highly resistant isolates, with MICs of ÏŸ8 g/ml, in the United Kingdom, Japan, and Belgium (9-11), while several others indicated a low to no increase in resistance, except for a few isolates, in Japan, the United States, and several European countries (6,(12)(13)(14)(15). Some of these studies involved isolates collected before 2005 (11, 13), but the majority referred to recent ones (6,9,10,12,14,15), suggesting a recent phenomenon. In the United Kingdom, a shift of resistance from an MIC 90 of 1 g/ml to one of 32 g/ml occurred during the last decade (9, 16).…”
mentioning
confidence: 99%
“…of veterinary importance (reviewed in reference 8), including M. bovis (9)(10)(11)(12)(13)(14)(15), the genetic background for decreased susceptibility has not been elucidated in either field isolates or mutants selected in vitro. M. bovis contains one or two rRNA operons (rrn).…”
mentioning
confidence: 99%
“…Fluoroquinolones are broad-spectrum antimicrobials, and enrofloxacin (ENR), orbifloxacin (ORB) and danofloxacin (DAN) have been approved for use in cattle in Japan. Fluoroquinolone minimum inhibitory concentrations (MICs) against Mb have previously been investigated [6,8]. Mb isolated from cattle in Japan showed various ENR MICs (range≀0.125-4 ”g/ml) [8].…”
mentioning
confidence: 99%
“…Fluoroquinolone minimum inhibitory concentrations (MICs) against Mb have previously been investigated [6,8]. Mb isolated from cattle in Japan showed various ENR MICs (range≀0.125-4 ”g/ml) [8]. Ten of eleven ENR-resistant (ENR MIC≄2 ”g/ml) Mb isolates derived from cattle in Israel carried 2 missense mutations within quinolone resistance-determining regions (QRDRs), causing the amino acid substitutions (AASs) Ser83Phe in GyrA and Asp84Asn in ParC [6].…”
mentioning
confidence: 99%